Developing Students' Narrative Writing Skill Through “Islamic Picture Series” in an Islamic Senior High School - Nurul Maghfirah; Sultan Baa (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
This study aimed to discover whether the use of Islamic Picture Series could improve the narrative writing skills of Islamic high school students in Makassar. The method of the study was pre-experimental with one group pre-test and post-test design. The population of the study was 10th Grade students of SMA IT Wahdah Islamiyah Putri Makassar, South Sulawesi in 2020/2021 academic year. Eighteen (18) students were selected as samples of the study using random sampling technique. The instrument of this study was a writing test which administered as a pre-test and post-test. Descriptive statistics was used to analyze the data. The results of data analysis showed that the post-test mean score was 91.8. This was greater than the pre-test mean score (87.2). Furthermore, the significant value of this study (0.000) was smaller than the alpha level (0.05). This means that H0 is rejected and H1 is accepted. Therefore, it can be concluded that Islamic picture series could be used as media in developing the students’ narrative writing skill of 10th Grades of SMA IT Wahdah Islamiyah. This study implies that Islamic Picture Series possesses a positive outcome towards fostering Islamic students’ writing skill in senior high school context.